2020
DOI: 10.1038/s41372-019-0586-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of vaccination during pregnancy and staphylococci concentration on the presence of Bacillus cereus in raw human milk

Abstract: Objective This study aimed to determine whether vaccination during pregnancy, prematurity, and staphylococci concentration influenced the presence of B. cereus or staphylococcal enterotoxins (SEs) in raw human milk from healthy mothers. Study design Human milk samples were collected from 152 healthy women. B. cereus, S. aureus and coagulase-negative staphylococci (CNS) were enumerated using selective agar culture media. The detection of B. cereus spores and SEs were determined using ELISA. Results CNS and B. c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…[128][129][130] Using culture-dependent methods, B. cereus was identified in 9.2% of 152 raw donor milk samples. 131 Donor milk is pasteurized for 30 min at 62.5°C, also known as the Holder method. 132,133 However, multiple studies have shown that this method is not always effective in killing Bacillus spores.…”
Section: Sporobiota Of Breast Milkmentioning
confidence: 99%
“…[128][129][130] Using culture-dependent methods, B. cereus was identified in 9.2% of 152 raw donor milk samples. 131 Donor milk is pasteurized for 30 min at 62.5°C, also known as the Holder method. 132,133 However, multiple studies have shown that this method is not always effective in killing Bacillus spores.…”
Section: Sporobiota Of Breast Milkmentioning
confidence: 99%
“…B. cereus is an opportunistic human pathogen associated with local and systemic infections in immunosuppressed patients. Premature infants are highly susceptible to infection due to their poorly developed immune system and prolonged invasive procedures, such as mechanical ventilation or catheterization [ 9 , 10 ]. Infections of the bloodstream, lungs, central nervous system [ 1 , 11 , 12 , 13 , 14 ], and intestinal tract [ 2 ] have been described, some with fatal outcomes [ 9 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lowering the incidence of necrotizing enterocolitis in newborns fed PBM compared to that in babies fed milk formula is a significant advantage for this type of feeding [ 6 ]. On the other hand, due to the immaturity of the immune system in extremely-low-birth-weight neonates, they are at risk of opportunistic infections, such as B. cereus [ 7 , 8 , 9 , 10 , 11 , 12 ]. While in healthy newborns, feeding with PBM is temporary support in cases of the mother’s delayed or insufficient lactation, in very-low-birth-weight neonates, PBM represents the only option because breastfeeding is not possible.…”
Section: Introductionmentioning
confidence: 99%